Abnormal expression of connective tissue growth factor and its correlation with fibrogenesis in adenomyosis. Issue 3 (March 2021) - Wang, Sha; Li, Bohan; Duan, Hua; Wang, Yiyi; Shen, Xue; Dong, Qianjing
Highlights: This study verified the expression of CTGF in ADS for the first time. CTGF is correlated with fibrogenesis and clinical symptoms. The expression of CTGF was high expression in the ectopic endometrium of ADS. CTGF may promote the proliferation of collagen fibers in the injurious myometrium. Mechanisms above cause the development of adenomyosis. Abstract: Research question: Does connective tissue growth factor (CTGF) expression relate to adenomyotic fibrosis and determine the correlation between fibrosis with adenomyosis-associated dysmenorrhoea? Design: Protein and mRNA expression of CTGF was detected by Western blots and real-time quantitative polymerase chain reaction in the endometrium of the control group and the eutopic and ectopic endometrium of the adenomyosis group. Collagen fibres and type I collagen in the myometrium were detected by immunohistochemistry and Masson's trichrome staining, and the correlations of CTGF protein and mRNA levels with the degree of fibrosis were analysed. Furthermore, the relationship between the severity of dysmenorrhoea and the degree of fibrosis was determined, and the correlation between uterus size and the degree of fibrosis was also analysed. Results: Levels of CTGF mRNA and protein were significantly higher in patients with adenomyosis than in controls, and CTGF mRNA and protein expression in adenomyosis was positively correlated with fibrosis severity (r = 0.57, P < 0.001 and r = 0.39, P = 0.012), which correlated positively with dysmenorrhoea and uterus size (r = 0.42 and r = 0.6, P < 0.002). Conclusions: Increased CTGF may contribute to the occurrence and fibrogenic progression of adenomyosis and may play an important role in dysmenorrhoea. The present study may provide ideas for treating adenomyosis-associated dysmenorrhoea.